Transformasi Pengelolaan Parkir Berlangganan 2027 Analisis Maslahah Mursalah terhadap Keadilan Distribusi Ekonomi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The policy plan to integrate parking fees into the Vehicle Registration Certificate (STNK), scheduled for nationwide implementation in 2027, has generated debate regarding contractual validity and fiscal justice. From the perspective of Islamic Economic Law, the transformation from a conventional pay-per-use retribution system to an annual prepaid system raises issues related to mutual consent (an-taradin) and the certainty of service benefits. This study aims to analyze the 2027 subscription parking policy using the framework of Maslahah Mursalah and the principle of distributive economic justice to assess its legitimacy as an instrument of public welfare. This research uses a normative legal method with conceptual and statutory approaches. Literature data are analyzed qualitatively through deductive reasoning to derive legal conclusions from general principles of Islamic economics in relation to contemporary fiscal policy. The findings indicate that the policy contains elements of Maslahah Mursalah, particularly in improving bureaucratic efficiency and preventing state revenue leakage (sadd adz-dzari'ah). However, from the perspective of distributive justice, the policy may contain elements of dzulm (injustice) if it is not supported by fair tariff segmentation. Without guaranteed service availability for all payers, mandatory annual parking fees risk being categorized as akl al-amwal bi al-bathil (unlawful appropriation of wealth). Therefore, a zoning-based tariff system is recommended to ensure fairness between obligations and benefits.